Scrolling to Speak: Exploring YouTube as a Medium to Boost Students’ Speaking Skills and Self-Confidence. - Dwi Rorowati (Greenation Education and Culture Review, 2025)
The rapid growth of digital media has transformed the way students learn English, particularly in developing speaking skills. One of the most widely used platforms among students is YouTube, which provides authentic language input through videos, dialogues, and real-life communication contexts. This study aims to explore the use of YouTube as a learning medium in boosting students’ speaking skills and self-confidence. The research employed a quantitative approach using a quasi-experimental design involving two groups: an experimental group taught using YouTube-based learning activities and a control group taught using conventional methods. The data were collected through speaking performance tests and self-confidence questionnaires. The results revealed that students who learned through YouTube showed significant improvement in both speaking skills and self-confidence compared to those in the control group. These findings suggest that YouTube can serve as an effective and engaging medium to enhance students’ oral communication ability and confidence in using English. Therefore, integrating YouTube into English language teaching is recommended to create a more interactive and motivating learning environment.